2021
DOI: 10.1002/ppul.25292
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of neuropeptides and obstructive airway disorder in infancy: A review with focus on post‐RSV wheezing and NEHI

Abstract: Obstructive airway disorders, common in infancy and early childhood, include some entities that are recognized to have neuro immune mediators as their underlying pathogenetic mechanisms. The best characterized example amongst post-viral wheezing phenotypes is the disorder that follows respiratory syncytial virus (RSV) infection and leads to intermittent, long-term wheezing. The underlying mechanisms of the airway reactivity related to RSV infection have been extensively studies and are associated with dysregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
0
4
0
1
Order By: Relevance
“…The % NEC area is twofold more remarkable in the proximal bronchioles [ 10 ]. NECs release bombesin, probably involved in the pathogenesis of small airway obstruction [ 29 ]. Mastej et al demonstrated that lung and airway appearances in patients with NEHI presented an increased anteroposterior diameter, suggesting that also this criterion might be considered in the diagnostic criteria [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The % NEC area is twofold more remarkable in the proximal bronchioles [ 10 ]. NECs release bombesin, probably involved in the pathogenesis of small airway obstruction [ 29 ]. Mastej et al demonstrated that lung and airway appearances in patients with NEHI presented an increased anteroposterior diameter, suggesting that also this criterion might be considered in the diagnostic criteria [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…We also did not assess for increased peptide levels (i.e., gastric releasing peptide). Elevations of these peptides can be expected in NEHI from overactive PNECs; however, the application of these levels is a more recently developed concept that is still actively undergoing research ( 20 , 34 ). Future studies may benefit from measuring peptide levels in these patients to further elucidate the pathophysiology of NEHI.…”
Section: Discussionmentioning
confidence: 99%
“…(24) Dalším vzácným onemocněním řazeným pod chILD je NEHI (neuroendocrine cell hyperplasia of infancy), dříve nazývaná perzistující tachypnoe kojenců. (25) Vzhledem k poměrně recentnímu popsání NEHI není příliš studií zabývajících se oxygenoterapií u tohoto onemocnění. Z dostupné literatury je ovšem patrné, že děti trpící tímto onemocněním vyžadují ve většině případů dlouhodobou oxygenoterapii.…”
Section: Intersticiální Plicní Onemocnění Dětíunclassified